Noninvasive brain stimulation and neural entrainment enhance athletic performance—a review - Colzato, L. S.; Nitsche, M. A.; Kibele, A. (Journal of Cognitive Enhancement, 2017)
Brain stimulation and neural entrainment relying on noninvasive techniques, applied to sports, might enhance brain activity in healthy athletes to improve their physical performance. In the past, several studies have employed stimulation procedures, either during athletic training or during separate sessions, to enhance physical and mental performance. Here, we review the available physiological and behavioral studies to clarify if and under which conditions noninvasive brain stimulation and neural entrainment might enhance athletic performance. Even though many studies suffer from small sample size, the results, compared to traditional training procedures, suggest advantages with regard to motor learning, motion perception, muscular strength, or decrements in muscle fatigue. Further, these techniques seem to be useful in fine-tuning crucial aspects of competitive sports such as speeding up the learning rate of specific motor skills. Although more research is needed to fully understand the effects of noninvasive brain stimulation and neural entrainment on athletic performance, we conclude that these emerging techniques are promising tools to enhance physical and mental performances in sports.